2013
DOI: 10.1007/s12288-013-0288-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of Wilms tumor 1 (WT1) gene Exon 7 mutations in-patient with cytogenetically normal acute myeloid leukemia

Abstract: This study aimed to assess the prognostic influences of Wilms tumor 1 (WT1) gene mutations in cytogenetically normal acute myeloid leukemia (CN-AML) among Egyptian patients. Exon 7 of WT1 was screened for mutations in samples from 82 CN-AML patients out of 203 newly diagnosed AML patients, using a high-resolution capillary electrophoresis. Seven out of 82 AML patients (8.3 %) harbored WT1 mutations. There was no significant difference between the mutant WT1 and wild type AML patients as regard age, sex, French… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Recently, WT1 zinc-nger mutations (exons 7-10) were detected in 8.3% of pediatric AML patients [12], 10.6% of AML patients with a normal karyotype (NK-AML) [32], and 13.6% of biallelic CEBPA mut AML patients [14]. We revealed that WT1 mutations occurred in 17.36% of CEBPA dm AML patients in exons 7, 8 and 9.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, WT1 zinc-nger mutations (exons 7-10) were detected in 8.3% of pediatric AML patients [12], 10.6% of AML patients with a normal karyotype (NK-AML) [32], and 13.6% of biallelic CEBPA mut AML patients [14]. We revealed that WT1 mutations occurred in 17.36% of CEBPA dm AML patients in exons 7, 8 and 9.…”
Section: Discussionmentioning
confidence: 79%
“…Mutations in WT1 affect normal hematopoiesis, cell cycle, apoptosis, transcription, and cell proliferation. 5 , 14 , 15 Previous studies have reported that WT1 was associated with poor outcomes and adverse response to treatment, especially the overexpression of WT1 at diagnosis, but different studies had different definitions of WT1 overexpression due to the various detection methods etc. 10 , 11 , 16 , 17 In addition, some studies have revealed that the high expression of WT1 was related to inv(16), NPM1 and 11q23 rearrangement, while the low expression of WT1 was related to t(8; 21).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to acute leukemia, mononuclear cells from bone marrow or peripheral blood of healthy volunteers did not express the WT1 gene at detectable levels ( Menssen et al, 1995 ; Padmakumar et al, 2021 ). Mutations in exons 7 and 9 of WT1 have been identified in acute myeloid leukemia and are related to poorer prognosis and resistance to treatment ( Aref et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%